1977
DOI: 10.1007/bf02586621
|View full text |Cite
|
Sign up to set email alerts
|

The value of gastrografin in the differential diagnosis of paralytic ileus versus mechanical intestinal obstruction

Abstract: Two cases in which serious intra-abdominal complications were masked by results of the contrast examination using Gastrografin were encountered. This caused the authors to review critically the use of Gastrografin in the differential diagnosis of paralytic ileus versus mechanical intestinal obstruction. In a series of 41 cases in which the diagnostic problem was not solved initially by means of physical examination and plain abdominal roentgenograms, the Gastrografin examination proved reliable in 28 (68 per c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
1
1

Year Published

1984
1984
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 7 publications
0
7
1
1
Order By: Relevance
“…Half of the patients were differently diagnosed with paralytic ileus, of which 2 patients had a definite mechanical obstruction, which was confirmed at reoperation. Different from the previous studies, Zer et al [21] reported that the use of Gastrografin provided a reliable diagnosis in 68.3% of controversial cases (28/41) when clinical signs and X-ray were inconclusive. …”
Section: Resultscontrasting
confidence: 43%
See 4 more Smart Citations
“…Half of the patients were differently diagnosed with paralytic ileus, of which 2 patients had a definite mechanical obstruction, which was confirmed at reoperation. Different from the previous studies, Zer et al [21] reported that the use of Gastrografin provided a reliable diagnosis in 68.3% of controversial cases (28/41) when clinical signs and X-ray were inconclusive. …”
Section: Resultscontrasting
confidence: 43%
“…In the early studies, the terminology of ‘postoperative paralytic ileus' was often used [13,14,21]. In the 90s, the nomenclature ‘postoperative ileus' (POI) started to be used in addition to ‘paralytic ileus' [2], and both of them have been found in recent studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations